Molecular regulators of smoltification and viral infection management tools for salmon aquaculture - McGowan, Michael John (University of Stirling, 2018)
Accurate smoltification and disease management in Atlantic salmon (Salmo salar) are key issues for the aquaculture industry. Due to their anadromous lifecycle the transfer of salmon from fresh water (FW) to seawater (SW) is crucial to their survival; too early can cause mortality, too late can cause desmoltification and long-term health problems. Both scenarios can increase susceptibility to four viral diseases: Salmon alphavirus (SAV), Infectious salmon anemia virus (ISAV), orthoreovirus (PRV), and Piscine myocarditis virus (PMCV). They all show similar clinical and histopathological symptoms and can easily spread throughout farms. Understanding the initial innate immune response to these viruses may provide biomarkers that could help identify and monitor infections. An in house and onsite Na+/K+ ATPase (NKA) qRT-PCR assay was developed for the salmon biomarker ATPase to test smoltification readiness in salmon smolts. Tested against NKA enzymatic assays it showed a similar success rate over 3 years: NKA qRT-PCR (57%), NKA activity assay (60%). Onsite tests confirmed that the ATPase mRNA transcript is a useful biomarker for smoltification detection. An in-lab and mobile multiplex qRT-PCR assay was developed for detection of SAV, PRV and PMCV. The analytical sensitivity of the SAV (86.5% SE 0.11), PRV (90.94%, SE 0.09) and PMCV (100.46%, SE 0.19) assays was 102 copies for PMCV and 103 for SAV and PRV. Initial results suggest individual assays could be run on site at farms. Addition of an internal control, probit analysis and viral positive tests are still required for multiplex assay integration. Salmon erythrocytes were infected with ISAV, SAV and Poly I:C to investigate whether they induce and up-regulate innate immune response genes. All genes were expressed at low levels in all parameters investigated including non-infected control erythrocytes. These findings suggest erythrocytes act as an initial buffer to viral infections and may help stimulate the innate immune response.